MiR224-5p Inhibitor Restrains Neuronal Apoptosis by Targeting NR4A1 in the Oxygen-Glucose Deprivation (OGD) Model - Liu, Ling-Ling; Qiao, Shan; Wang, Mei-Ling; Wu, Huai-Kuan; Su, Yong-Xin; Wang, Ke-Mo; Liu, Xue-Wu (Frontiers in Neuroscience, 2020)
This study was designed to investigate the molecular mechanism of stroke and to explore the effect of miR-224-5p in hypoxic cortical neurons. Firstly, we established a middle cerebral artery occlusion (MCAO) model with Sprague-Dawley rats. Triphenyltetrazolium chloride (TTC) staining showed the brain infarction of MCAO rat. Longa Scores of rats were significantly increased in the 12th, 24th, and 48th hours after MCAO. Then, we found miR-224-5p was increased after MCAO in rats by qRT-PCR. In order to investigate the effect of miR-224-5p in hypoxic neurons, we established an oxygen-glucose deprivation (OGD) model with cortical neurons. MiR-224-5p was also up-regulated in neurons after OGD by qRT-PCR. After transfection of miR-224-5p inhibitor, the number of neurons in anti-miR-224-5p group significantly increased (P<0.01) in comparison to anti-NC group. Furthermore, Tuj1+ (neuronal marker) staining and TUNEL assay (to detect apoptotic cells) were performed in neurons. The survival of neurons in the anti-miR-224-5p group was significantly improved (P<0.01), while the apoptosis of neurons in the anti-miR-224-5p group was significantly decreased (P<0.01), when compared with the anti-NC group. In addition, we predicted that potential target genes of miR-224-5p were Nuclear Receptor Subfamily 4 Group A Member 1 (NR4A1), Interleukin 1 Receptor Antagonist (IL1RN), and Ring Finger Protein 38 (RNF38) with bioinformatics database, such as TargetScan, miRDB, miRmap and miRanda. The result of qRT-PCR confirmed that NR4A1 was significantly decreased after hypoxic injured (P<0.01). Meanwhile, luciferase reporter’s assay indicated that NR4A1 was the direct target of miR-224-5p. Compared with anti-miR-224-5p+siNC group, the number of cortical neurons and the length of neuron axon in anti-miR-224-5p+si-NR4A1 group was significantly decreased (P<0.01), the number of neuronal apoptosis in anti-miR-224-5p+si-NR4A1 group was increased (P<0.01). In conclusion, miR-224-5p played a crucial role in the hypoxic neuron injury through NR4A1, which might be an important regulatory mechanism in OGD injury of neurons.